Adsorption of Carbamazepine on the Adsorbent Produced from Spent Bleaching Earth - Mahramanlioglu, Mehmet; Ozgen Onnar, Ozge (Asian Journal of Chemistry, 2012)
The adsorption of carbamazepine on the adsorbent produced from spent bleaching earth was studied as a function of time, pH and initial concentration. The adsorption equilibrium was achieved within 1 h and the adsorption kinetics was found to obey the first-order Lagergren equation. The rate constants and intraparticle diffusion constants were calculated. It was seen that pH effect on the adsorption of carbamazepine is not very significant. It was concluded that activated carbon produced from spent bleaching earth can be considered as an effective adsorbent for removing carbamazepine.